What really matters in operations management : the 8th International Conference of the European Operations Management Association, Bath, UK - Maylor, Harvey (International journal of operations & production management, 2003)
What really matters in operations management?''What really matters in operations management'' provided the theme for the 8thInternational Conference of the European Operations Management Association.We welcomed over 220 delegates from 26 countries to Bath for the opening of theconference.